Development of sensors for the detection of clinically relevant substances using molecular imprinting - Fowler, Steven A. (Cranfield University, 2009)
This thesis investigates the development of sensing devices based on molecularly imprinted polymers for the detection of clinically relevant analytes. Three analytes were considered, metronidazole, creatinine and propofol. A molecularly imprinted polymer (MIP) was computationally designed for metronidazole and tested using SPE techniques. This polymer was then grafted onto a transducer surface using an immobilised initiator. Amperometric and impedance detection of metronidazole were investigated. The capacitive detection of creatinine was reproduced from the literature (Panasyuk- Delaney et al., 2002) as this approach could be applied to other MIPs to form a universal platform for sensor development. However, the sensors produced using this methodology were difficult to reproduce and attempts to improve them were unsuccessful. A model for capacitive electrodes was developed to explain the obtained results. To address the key challenges found in the aforementioned work, a dual polymerisable monomer was used as a conductive anchor for the amperometric and impedance detection of propofol. The developed amperometric sensors demonstrated very high sensitivity (limit of detection was below 5 µM), although the electrodes lacked in selectivity. In conclusion, this thesis illustrates some of the key areas which need to be considered in the development of MIP-based devices and investigates some innovative solutions to these problems.